Metanephric Adenoma–Epithelial Wilms Tumor Overlap Lesions: An Analysis of BRAF Status. (September 2019) - Wobker, Sara E.; Matoso, Andres; Pratilas, Christine A.; Mangray, Shamlal; Zheng, Gang; Lin, Ming-Tseh; Debeljak, Marija; Epstein, Jonathan I.; Argani, Pedram
Abstract : Metanephric adenoma (MA) has historically been considered to represent a differentiated form of epithelial Wilms tumor (WT), based in part upon cases that morphologically overlap these 2 neoplasms. More recently, BRAF V600E mutations have been demonstrated in the majority of MAs but not in unselected or even epithelial-predominant WTs, suggesting 2 genetically distinct entities. However, no prior study has examined BRAF status in neoplasms with overlapping histologic features of epithelial WT and MA. We studied a cohort of 11 such overlapping lesions, 2 of which we considered morphologically to be otherwise typical MAs with unusually prominent mitotic activity and 9 of which we classified as epithelial WTs with areas resembling MA. Both mitotically active MAs demonstrated the BRAF V600E mutation. While the majority (5/9) of epithelial WTs with areas resembling MA were negative for BRAF V600E mutation, 4 such cases were positive. Two BRAF V600E mutation-positive WTs occurred in children. One case in a 6-year-old male was morphologically similar to the BRAF V600E mutation-positive adult cases and subsequently metastasized to the lungs; remarkably, the metastases then completely resolved on Braf targeted therapy. A second occurred in a 3-year-old girl whose posttherapy nephrectomy specimen's tumor was encapsulated and mitotically active like a typical WT, but also had more differentiated areas resembling MA. Immunohistochemistry for Braf V600E paralleled the molecular findings, demonstrating immunoreactivity in both the WT and MA-like areas of all 4 of these neoplasms. In summary, we demonstrate that BRAF V600E mutations are not entirely restricted to typical MA, as they may be seen in MAs showing mitotic activity along with a subset of epithelial-predominant WTs in adults and children that have foci which overlap morphologically with MA.